Comparison of shariah stock screening methodology between Malaysia and International / Eirfan Syamil Ahmad Norisham - Ahmad Norisham, Eirfan Syamil (Universiti Teknologi MARA, Selangor, Puncak Alam Campus, 2018)
Shariah is an Islamic law derived from the divine revelation and practice of the prophet namely, al-Quran and al-Hadith. Shariah prohibits elements such as usury (riba’), gambling (maysir) and uncertainty (gharar). These elements are present in many conventional financial activities. For a Muslim, this means getting involved indirectly in prohibited practices, which is considered as a grave sin. To tackle this problem, Shariah scholars have set some acceptable boundaries for companies to do their business activities and outline steps to purify the sinful earnings. Thus, the purpose of this paper is to compare the criteria used among Islamic Indices, specifically between the FTSE Global Islamic Index (FTSE) and the Dow Jones Islamic Market Index (DJIM) in screening a permissible company for investment purposes. A comparative analysis is performed to highlight the variances of the Shariah-compliant methods and principles practiced by these renowned institutions with the latest compiled data. The two controversial criteria examined are level of debt and level of liquidity of the company. This paper will discuss the criteria, processes as well as the matters involved in the screening for Shariah-compliant and. Two sets of business screens and financial screens are profiled separately to clearly examine the similarities and differences between the different methodologies. Some of these practitioners are more specific in their listing of Shariah-impermissible activities, while some are more general in allowing more businesses to be included as permissible. The majority of these users practice a two-tier method of screening which is qualitative and quantitative. Under the quantitative screen, the range of allowable threshold ratios on non-permissible criteria differs slightly between them.